Comparative Federalism and Covid-19 Combating the Pandemic - Steytler, Nico (Routledge Studies in Federalism and Decentralization, 2022)
This comprehensive scholarly book on comparative federalism and the Covid-19 pandemic is written by some of the world's leading federal scholars and national experts. The Covid-19 pandemic presented an unprecedented emergency for countries worldwide, including all those with a federal or hybrid-federal system of government, which account for more than 40 per cent of the world's population. With case studies from 19 federal countries, this book explores the core elements of federalism that came to the fore in combatting the pandemic: the division of responsibilities (disaster management, health care, social welfare, and education), the need for centralisation, and intergovernmental relations and cooperation. As the pandemic struck federal countries at roughly the same time, it provided a unique opportunity for comparative research on the question of how the various federal systems responded. The authors adopt a multidisciplinary approach to question whether federalism has been a help or a hindrance in tackling the pandemic. The value of the book lies in understanding how the Covid-19 pandemic affected federal dynamics and how it may have changed them, as well as providing useful lessons for how to combat such pandemics in federal countries in the future. This book will be of great interest to students and scholars of politics and international relations, comparative federalism, health care, and disaster management.